Ceos On the Edge: Earnings Manipulation and Stock-Based Incentive Misalignment - Zhang, Xiaomeng; Bartol, Kathryn M.; Smith, Ken G.; Pfarrer, Michael D.; Khanin, Dmitry M. (Academy of Management Journal, 2008)
Synthesizing agency theory and prospect theory, we examined the effects of stock-based incentives on CEO earnings manipulation behaviors. In analyses of data compiled from the public companies listed in Compustat's Executive Compensation Database and a U.S. General Accounting Office restatements database, we found that CEOs were more likely to manipulate firm earnings when they had more out-of-the-money options and lower stock ownership. Firm performance and CEO tenure interacted with out-of-the-money options and ownership to influence CEO earnings manipulation behaviors. Our findings inform agency-based views by providing evidence that, under certain conditions, stock-based managerial incentives lead to incentive misalignment.